EXPLORING STUDENT’S PERSPECTIVES TOWARD CLARITY AND FAMILIARITY OF SPEAKING SCORING RUBRICS - Abdusalomova Farangis Obidovna (Western European Studies, 2024)
This study investigates the role of speaking rubrics in fostering student learning and engagement, with a particular focus on student perspectives regarding rubric clarity and familiarity. Through a survey of 100 students at Samarkand State Institute of Foreign Languages, the research explores student perceptions of the strengths and weaknesses of their speaking skills. While students demonstrate a strong understanding of effective speaking qualities like fluency and vocabulary, the findings reveal a potential underestimation of the importance of rubric-assessed skills like organization and delivery. The analysis emphasizes the importance of incorporating student feedback into rubric development to create assessment tools that promote transparency, self-directed learning, and student empowerment. By prioritizing clarity and user-friendliness, rubrics can evolve from mere evaluation tools into instruments that actively guide and support student growth in oral communication skills
Keywords: speaking skills; survey report; English language competence